Multiple Input Multiple Output Visible Light Communication System Sub-Optimization Using Power Allocation Schemes - Elewah, Ibrahim Ahmed Mohamed Elsayed (2025)
Low power consumption and high bit rate are the most important features of visible light communication (vlc) systems. These features are always the main target of any communication system. This study focuses on enhancing data rates and optimizing power consumption in vlc systems. To improve the data rate, multipleinput multiple-output (mimo) has been employed and this technique has an inherited property of combining the data streams and multiplying the data rate. The system was upgraded from a 2×2 to a 4×4 mimo-vlc configuration. To optimize power consumption, two power allocation schemes, gain ratio power allocation (grpa) and normalized gain difference power allocation (ngdpa), were applied to the 4×4 mimo-vlc system. Additionally, a novel modified-ngdpa (m-ngdpa) scheme was proposed, extending the coverage area from 3.14 m² to 4.52 m² and enhancing the sum rate at the coverage boundaries. The mathematical model of the proposed system was presented. The simulation result shows that the 4×4 mimo-vlc system achieves a sum rate of 268 mbps over a 10 mhz bandwidth within a circular coverage area of 1 m radius (3.14 m²). Simulation results indicate that while ngdpa provides a higher sum rate, grpa demonstrates better overall energy efficiency.